Kualitas Mikrobiologi Cacing Laor (Polychaeta) dari Perairan Pantai Lawena, Desa Hutumury Kota Ambon.: Micobiologicaly Quality Of “Laor” Worms (Polychaeta) From Lawena Beach, Village Hutumury Ambon City - Meigy Nelce Mailoa; Raja Bonan Dolok Sormin; Joel Lewaherilla (Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2020)
“Laor” worms were organisms that originated at the base of the waters, for that reason, sometime it is possible contaminated by pathogenic bacteria. This study aims to determine the quality characteristics of “Laor” worms. This research was using the descriptive method in the form of morphological characterization, and biochemical tests on the isolates of lactic acid bacteria (LAB) and Vibrio sp of “laor” worms. The result showed the total bacteria, LAB, and Vibrio sp contained in fresh “laor” worms were (1.2x104-1.6x104) CFU/g; (6.8x104-7.4x104) CFU/g, and (6.0x103-7.0x103) CFU/g respectively. Morphological and biochemical characterization found that LAB isolates have a rounded colony shape, small size, milky white color with convex elevation, round cell shape, short chain (Isolate Bl 6), short stem cell shape (isolate Bl 2, Bl 3, Bl 4) , the shape of short chain stem cells (isolate Bl 3) and an isolates of Vibrio colonies are rounded shape (isolates Vb1, Vb2, Vb3 and Vb6, Vb4), An isolate of Vb5 has an irregular colony shape, yellow colored with a smooth texture. Interpretation results of catalyses test of the two isolates showed positive and Gram staining of LAB isolates was Gram positive while Vibrio Isolate was Gram negative. This finding can be used as a basis for continued of microbiological testing related to bacterial pathogenicity that isolated from “laor” worms.